Perioperative Neurological Evaluation and Management to Lower the Risk of Acute Stroke in Patients Undergoing Noncardiac, Nonneurological Surgery: A Scientific Statement From the American Heart Association/American Stroke Association. Issue 19 (8th April 2021) - Benesch, Curtis; Glance, Laurent G.; Derdeyn, Colin P.; Fleisher, Lee A.; Holloway, Robert G.; Messé, Steven R.; Mijalski, Christina; Nelson, M. Timothy; Power, Martha; Welch, Babu G.; ,
Abstract : Perioperative stroke is a potentially devastating complication in patients undergoing noncardiac, nonneurological surgery. This scientific statement summarizes established risk factors for perioperative stroke, preoperative and intraoperative strategies to mitigate the risk of stroke, suggestions for postoperative assessments, and treatment approaches for minimizing permanent neurological dysfunction in patients who experience a perioperative stroke. The first section focuses on preoperative optimization, including the role of preoperative carotid revascularization in patients with high-grade carotid stenosis and delaying surgery in patients with recent strokes. The second section reviews intraoperative strategies to reduce the risk of stroke, focusing on blood pressure control, perioperative goal-directed therapy, blood transfusion, and anesthetic technique. Finally, this statement presents strategies for the evaluation and treatment of patients with suspected postoperative strokes and, in particular, highlights the value of rapid recognition of strokes and the early use of intravenous thrombolysis and mechanical embolectomy in appropriate patients.